Multifunctional materials: concepts, function-structure relationships, knowledge-based design, translational materials research. Issue 1 (28th August 2018) - Lendlein, Andreas; Trask, Richard S
Abstract: Integrating different functions in one material system is a fundamental challenge, especially if those functions seem to exclude each other. Understanding function-structure relationships and developing a competence in the system approach for multifunctionality enables many modern applications, which can improve quality of life and address important global challenges. The interdisciplinary field recently extends to computational engineering approaches for virtual material design and to advanced fabrication schemes taking advantage of digitalisation. In this way development cycles can be shortened and products based on multifunctional materials can become more and more adaptive and individualised. It is against this backdrop that Multifunctional Materials has been launched, in consultation with the scientific community, to become a selective journal focused on conceptual novelty that will uniquely bring together all aspects of this rapidly developing field.